Asian development outlook 2018 update maintaining stability amid heightened uncertainty. (Asian Development Outlook Series., 2018)
Developing Asias gross domestic product is forecast to expand by 6.0% in 2018 and 5.8% in 2019. Consumer prices for 2018 and 2019 are projected to rise by 2.8%.